Ecotoxicology: A Comprehensive Treatment - Newman, Michael (CRC Press, 2009)
Integrating ecotoxicological concepts across a range of hierarchical levels, Ecotoxicology: A Comprehensive Treatment focuses on the paradigms and fundamental themes of ecotoxicology while providing the detail and practical application of concepts often found in more specialized books. By synthesizing the best qualities of a general textbook and the narrower, more specific scope of a technical reference, the authors create a volume flexible enough to cover a variety of instructional vantages and thorough enough to engender a respect for the importance of understanding and integrating concepts from all levels of biological organization.